A Review: Traditional Use, Phytochemical and Pharmacological Review of Red Betel Leaves (Piper Crocatum Ruiz & Pav) - Suri, Melani Antika; Azizah, Zikra; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Red betel leaf (Piper crocatum Ruiz & Pav) is a plant that grows in tropical areas and was previously known as an ornamental plant, but was later used as a medicinal plant. The use of red betel leaf (Piper crocatum Ruiz & Pav) is traditionally beneficial in curing diseases such as thrush and toothache. Meanwhile, red betel leaf decoction, which is antiseptic, can act as a mouthwash, prevent bad breath and eliminate body odor. From chromatography, it is known that red betel leaves contain flavonoids, polyphenolic compounds, tannins, and essential oils. In the use of red betel leaves, it is widely used to get rid of body odor, vaginal discharge, ulcer, fatigue, muscle aches, and to smoothen the skin, as well as for itchy, red eye cleansers, and canker sore. Red betel leaves decoction is also believed to be able to eliminate bad breath in the mouth if used as a mouthwash.